Differential NtcA Responsiveness to 2-Oxoglutarate Underlies the Diversity of C/N Balance Regulation in Prochlorococcus - Domínguez-Martín, María A.; López-Lozano, Antonio; Clavería-Gimeno, Rafael; Velázquez-Campoy, Adrián; Seidel, Gerald; Burkovski, Andreas; Díez, Jesús; García-Fernández, José M. (Frontiers in Microbiology, 2018)
Introduction The extraordinary abundance of Prochlorococcus in the oligotrophic areas of the oceans has been reported by different studies since its discovery (Chisholm et al., 1988), and it is considered that Prochlorococcus contributes significantly to the global primary production (Goericke and Welschmeyer, 1993; Liu et al., 1997; Casey et al., 2007), conferring this organism an outstanding importance in marine ecology (Biller et al., 2015). Recent reports suggest it might become even more widespread due to global warming in the near future (Flombaum et al., 2013). Different explanations have been proposed for the abundance of Prochlorococcus, including the very small size of the cells, the high surface/volume ratio or the streamlining of the genome (and consequently of the metabolic pathways), leading to low energetic requirements for survival and cell division (Partensky et al., 1999; Giovannoni et al., 2014; Biller et al., 2015). Adaptation to oligotrophic oceans involves the development of adaptive mechanisms to cope with the availability of several key elements, which are scarce in those regions. Nitrogen is one of them. This fact has led to different strategies to optimize its utilization in marine cyanobacteria, providing enough nitrogen for growth with an affordable energetic expense, such as the use of specific sets of N-assimilating genes depending on the strain (López-Lozano et al., 2002; Moore et al., 2002; Dufresne et al., 2003; Palenik et al., 2003; Rocap et al., 2003; García-Fernández et al., 2004; Dufresne et al., 2008; Scanlan et al., 2009; Berube et al., 2014; Biller et al., 2014). The cyanobacterial regulatory mechanisms to control the C/N balance are present in Prochlorococcus, but showing some striking variations with respect to freshwater strains: despite possessing the genes involved in standard carbon/nitrogen regulation in cyanobacteria (namely ntcA, glnB and pipX encoding, respectively, NtcA, PII and PipX), they do not seem to work as previously described (Lindell et al., 2002; Palinska et al., 2002; García-Fernández et al., 2004; López-Lozano et al., 2009; Domínguez-Martín et al., 2014). Besides, the regulation of enzymes such as glutamine synthetase (GS) (El Alaoui et al., 2001; Gómez-Baena et al., 2001; El Alaoui et al., 2003) and isocitrate dehydrogenase